Hospital Academic Status and Value of Care for Nonmetastatic Colon Cancer - Veenstra, Christine M. (J Oncol Pract, 2015)
PURPOSE: The relationship between oncologic hospital academic status and the value of care for stage II and III colon cancer is unknown. METHODS: Retrospective SEER-Medicare analysis of patients age ≥ 66 years with stage II or III colon cancer and seen by medical oncology. Eligible patients were diagnosed 2000 to 2009 and followed through December 31, 2010. Hospitals reporting a major medical school affiliation in the NCI Hospital File were classified as academic medical centers. The association between hospital academic status and survival was assessed using Kaplan-Meier curves and Cox proportional hazards models. The association with mean cost of care was estimated using generalized linear models with log link and gamma family and with cost of care at various quantiles using quantile regression models. RESULTS: Of 24,563 eligible patients, 5,707 (23%) received care from academic hospitals. There were no significant differences in unadjusted disease-specific median survival or adjusted risk of colon cancer death by hospital academic status (stage II hazard ratio = 1.12; 95% CI, 0.98 to 1.28; P = .103; stage III hazard ratio = 0.99; 95% CI, 0.90 to 1.08; P = .763). Excepting patients at the upper limits of the cost distribution, there was no significant difference in adjusted cost by hospital academic status. CONCLUSION: We found no survival differences for elderly patients with stage II or III colon cancer, treated by a medical oncologist, between academic and nonacademic hospitals. Furthermore, cost of care was similar across virtually the full range of the cost distribution.